Antioxidant and cytotoxic activities of carob tree fruit pulps are strongly influenced by Gender and cultivar - Custódio, Luísa (2015)
Extracts from fruit pulps of six female cultivars and two hermaphrodite Portuguese carob trees [(Ceratonia siliqua L., Fabaceae)] exhibited strong antioxidant activity and were rich in phenolic compounds. The extracts decreased the viability of different human cancer cell lines on a dose- and time-dependent manner. Gender and cultivar significantly influenced the chemical content and the biological activities of the extracts. Extracts from hermaphrodite trees had a higher content of phenolic compounds, and exhibited higher antioxidant and cytotoxic activities. Among. females, cv. Aida had the highest radical scavenging activity and total content of phenolics, Mulata the highest capacity to inhibit lipid oxidation and Gasparinha the strongest cytotoxic activity on HeLa cells. The decrease in cell viability was associated with apoptosis on HeLa and MDA-MB-231 lines. (+)-Catechin and gallic acid (GA) were the main compounds identified in the extracts, and GA contributed to the antioxidant activity. Our results show that the antioxidant and cytotoxic activities of carob tree fruit pulps are strongly influenced by gender and cultivar, and provide new knowledge about the advantages of hermaphrodite trees over female cultivars, namely, as a source of compounds with biological interest, which may represent an increase of their agronomic interest.